Performance study on the effect of different exhaust length for motorcycle engine - Abdul, Mohd Rizan (2015)
This research provides an overview of the performance on the effect of the different exhaust length for motorcycle engine. The research also covers the effect in terms of emissions. The engine used was a motorcycle 125cc 4-stroke gasoline engine. There are two method was used; experiment and simulation. For experiment, load applied to the engine with different lengths of exhaust pipe. The engine speed of this study was controlled in the range of 800 – 1000 rpm. The test engine has been attached to the dynamometer. The engine specifications and measured components of exhaust system were used for modelling and visualization using GT-Power simulation software. The different length of exhaust will be used for the simulation. Brake power, brake mean effective pressure (BMEP) and brake specific fuel consumption (BSFC) of the engine are discussed as the performance of the engine. Besides that carbon dioxide (CO2), carbon monoxide and hydrocarbon (HC) was discussed as the emissions of the engine. The performance test was conducted to investigate the different lengths of exhaust manifold will affect the engine performance and exhaust-out emissions